Négritude em dois tempos: emergência e instituição de um movimento (1931-1956) - Raissa Brescia dos Reis (2014)
Through the reading and analysis of the dominant literature written since the mid-twentieth century on the central object of this master's project, namely the movement of Négritude thought in two moments of its institutionalization, between and after the two World Wars, in the period of 1931 to 1956, this text seeks to shape the trajectory of the movement itself and also of a homogeneous speech made about it and its place of origin within the establishment of the field of a Black-African Literature. Through reading and systematization of the canonical works of Négritude movement, this paper has focused efforts on the perception of the central, founding elements of this group in its relation to the sociability networks deployed around the neologism in the 1930s and also in the 1940s and 1950s, when new thinkers and new causes and possibilities of dialogue came to the city of Paris, institutionalizing and naming a new French-speaking intellectual community.